THE FIRST EXPERIENCE OF USING LAPAROSCOPIC GAMMA PROBE FOR INTRAOPERATIVE VISUALIZATION OF SENTINEL LYMPH NODES IN GYNECOLOGICAL CANCER - M. O. Ochirov; L. A. Kolomiets; V. I. Chernov; I. G. Sinilkin; A. L. Chernyshova; A. B. Villert; S. V. Molchanov; O. N. Churuksaeva; A. Yu. Kishkina (Сибирский онкологический журнал, 2018)
Visualization of sentinel lymph nodes (SLN) is now widely accepted for lymph node (LN) detection using a radioactive lymphotropic trace. Preoperative lymphoscintigraphy with intraoperative lymphatic mapping under gamma detecting probe guidance proved to be an easy and reliable method for SLN detection.Material and methods. In this article we present our experience in using laparoscopic gamma-probe for intraoperative visualization of sentinel lymph nodes in gynecological cancer.Results. Intraoperative visualization of sentinel lymph nodes in young cervical cancer patients and in patients with stage I endometrial cancer allowed us to perform radical surgery with personalization of the extent of lymph node dissection, especially for patients with low and intermediate risks of lymphogenic metastasis.